On‐Demand Autophagy Cascade Amplification Nanoparticles Precisely Enhanced Oxaliplatin‐Induced Cancer Immunotherapy. Issue 32 (28th June 2020) - Wang, Xuhui; Li, Man; Ren, Kebai; Xia, Chunyu; Li, Jianping; Yu, Qianwen; Qiu, Yue; Lu, Zhengze; Long, Yang; Zhang, Zhirong; He, Qin
Abstract: Chemoimmunotherapy‐induced antitumor immune response is highly dependent on tumor autophagy. When tumor cells are treated with chemoimmunotherapy, timely overactivated autophagy can not only lead more tumor cells to death, but also participate in the endogenous antigen presentation and immune stimulators secretion of dying cells, thus plays a vital role. However, timely and accurately overactivated tumor autophagy during chemoimmunotherapy is of great difficulty. Here, an on‐demand autophagy cascade amplification nanoparticle (ASN) is reported to boost oxaliplatin‐induced cancer immunotherapy. ASN is prepared by self‐assemble of autophagy‐responsible C‐TFG micelle and is followed by electrostatic binding of oxaliplatin prodrug (HA‐OXA). After entering tumor cells, the HA‐OXA shell of ASN first responds to the reduction microenvironment and releases oxaliplatin to trigger tumor immunogenic cell death and mildly stimulates tumor autophagy. Then, the exposed C‐TFG micelle can sensitively respond to oxaliplatin‐induced autophagy and release a powerful autophagy inducer STF‐62247, which precisely transforms autophagy to "overactivated" condition, leading tumor cells to autophagic death and enhance subsequent tumor antigen processing of the dying cells. In CT26 tumor‐bearing mice, ASN exhibits optimal immune stimulation and antitumor efficiency due to its on‐demand autophagy induction ability. Abstract : An on‐demand autophagy cascade amplification nanoparticle (ASN) is established to intelligently boost oxaliplatin (OXA)‐induced immunotherapy of cancer cells. Upon arrival at a tumor site, the ASN first releases OXA to trigger tumor immunogenic death and stimulates autophagy. Then, the ASN can respond to the OXA‐induced autophagy and further overactivate autophagy, which not only leads to tumor autophagic death but also enhances immune cell recruitment.